1, 2, 4‐Triethylbenzene1) [MAK value documentation, 2018]. Issue 3 (25th July 2019) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has evaluated 1, 2, 4‐triethylbenzene [877‐44‐1 ], considering all toxicological endpoints. Available publications are described in detail. In subchronic oral studies 1, 2, 4‐triethylbenzene causes axonopathy of peripheral nerves in rats and mice. A NOAEL was not obtained. The structurally related 1, 2‐diethylbenzene leads to the same neurotoxic effects which are determined by oxidation of the 1, 2‐diethyl groups to a gamma‐diketone. The formation of a gamma‐diketone is possible and indirectly shown with 1, 2, 4‐triethylbenzene and the mechanism of neurotoxicity is assumed to be the same for both compounds. Due to the limited data with 1, 2, 4‐triethylbenzene, the better investigated 1, 2‐diethylbenzene, which is about 5 times as toxic, is used as a read‐across. As a maximum concentration at the work place (MAK value) of 1 ml/m 3 has been set for 1, 2‐diethylbenzene, a MAK value of 5 ml/m 3 for 1, 2, 4‐triethylbenzene is established. Since a systemic effect is critical, Peak Limitation Category II is designated. Peripheral neurotoxicity is a cumulative effect and an excursion factor of 8 would be adequate. However, the NOEAC for airway and eye irritation is not known and therefore an excursion factor of 2 is set. Thus, the allowable peak exposures are lower than those of other alkyl benzenes. There are no developmental toxicity studies. Therefore, 1, 2, 4‐triethylbenzene is assigned to Pregnancy Risk Group D. There are no data on genotoxicity, carcinogenicity and sensitization. According to skin absorption models, percutaneous absorption can contribute significantly to systemic toxicity and 1, 2, 4‐triethylbenzene is designated with an "H" notation.